A PILOT STUDY OF A MULTICOMPONENT OBESITY INTERVENTION IN OLDER, RURAL ADULTS WITH OBESITY. (11th November 2018) - Batsis, J; Al-Nimr, R; Pidgeon, D; Cook, S; Jensen, M; Clark, M; Mackenzie, T; Bartels, S
Abstract: Background:Obesity in older adults is an emerging public health challenge. Older obese persons aged 65 years residing in rural areas have reduced access to weight management programs due to geographic distances that impede their ability to improve their physical function. Methods: This project was a 12-week pilot intervention in nine older adults with obesity (body mass index (BMI)≥30) between September and December 2017 in a geographically isolated area in Northern New England. The structured intervention consisted of individualized, weekly registered dietitian visits focusing on behavioral modification and caloric restriction with twice weekly physical therapist-led group strengthening training classes in a community-based aging center. An aerobic activity prescription outside these sessions was provided.Monthly study measures assessed outcomes of weight and function, analyzed using descriptive statistics and repeated measures ANOVA. Results:Mean age was 71.5 ± 5.1years (67% female).Individuals completed 100% of all study assessments, attended 88.4% of all possible PT classes (range 79.2–95.8) and 88.9% (range 61.5–100%) of all nutrition sessions. Level of satisfaction for the overall intervention (5-point Likert) was high (88.9% rating very satisfied). Weight decreased from 93.7 ± 9.7 to 89.4 ± 4.0kg (p<0.001). Mean BMI and waist circumference decreased, respectively, from 35.4 ± 3.4 to 33.7 ± 3.8(p<0.001), and 116.3 ± 7.5 to 108.7 ± 9.2cm (p<0.001). Grip strength, gait speed, and 5-times sit-to-stand time improved from 27.2 ± 8.4 to 32.0 ± 8.8kg (p=0.006), 1.16 ± 0.21 to 1.35 ± 0.23 m/s(p=0.01), and 12.5 ± 4.0 to 9.6 ± 1.7s(p=0.003). Conclusions:A multicomponent obesity intervention is feasible and acceptable to older adults with obesity, despite geographic restrictions. The intervention holds promise in promoting weight loss with a corresponding improvement in physical function in older adults.